الاعتداد بجزء العلة في الإعلال وعدمه (دراسة صرفية) - حسام محمد عبدالرحيم محمد (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2025)
يتناول هذا البحث: الاعتداد بجزء العلة في الإعلال وعدمه (دراسة صرفية)، ويعنى بدراسة أثر جزء العلة الموجبة للإعلال وجودًا وعدمًا في تحقق الإعلال وعدمه، من خلال نماذج تطبيقية متعددة، وقد اتبعت في هذا البحث المنهج الوصفي القائم على الاستقراء والوصف التحليلي لعدد من النماذج الصرفية، وقد انتهى البحث إلى عدد من النتائج يأتي في مقدمتها: اشتمال النماذج الصرفية في مبحث الإعلال على عدد من الأمثلة والصور التي  يثبت فيها الإعلال اعتمادًا على جزء العلة، في مقابل صور ونماذج أخرى يمتنع فيها الإعلال لعدم اكتمال العلة والاقتصار على أحد جزأيها. This study investigates whether or not part of the cause (ʿillah) should be considered in cases of ʾiʿlāl (phonological substitution) from a morphological perspective. It focuses on examining the role of partial causation in determining whether ʾiʿlāl occurs or not. The study analyzes multiple applied models using a descriptive approach based on inductive and analytical examination of selected morphological examples. The research concludes with several findings, foremost among them: the morphological models within the topic of ʾiʿlāl contain numerous instances and forms where substitution is validated based on partial causation, in contrast to other forms where substitution is excluded due to the incompleteness of the cause, relying only on one of its components.